Archiving the cultural legacy of mbira dzavadzimu in the context of kuriva guva and dandaro practices - Matiure, Perminus (University of Kwazulu Natal, 2017)
This thesis focuses on archiving cultural legacy of Shona mbira dzaVadzimu in the context of kurova guva and dandaro practices. The study is informed by archive theory which provides insights on how to collect and archive tangible materials. Alongside the archive theory, the study also employs Shelemay’s theory which discusses how traditions undergo change as they are transmitted from the past to the present and the role of ethnomusicologists in preserving legacies that are affected by the change. This theory assists in discussing the changes that have taken place in Shona kurova guva practices and how they have led to a decline in the sacred use of mbira dzaVadzimu. In order to collect empirical data about kurova guva and mbira dzaVadzimu, an ethnographic paradigm is employed in which participants are selected using purposive sampling technique from a population of all culture bearers, mbira maker and players, pastors and archivists in Gweru urban and Hwedza District. Face to face interviews, field notes, participant observation method and video recordings are used to solicit data about mbira dzaVadzimu and kurova guva ceremony. In this study I argue that while mbira dzaVadzimu has gained popularity within and outside Zimbabwe, the migration of mbira players from rural to urban together with the change in perceptions about mapira ceremonies like kurova guva by the Shona have subsequently led to the decline in the sacred use of the cultural legacy of mbira dzaVadzimu in the Shona cosmology. In order to preserve the legacy an applied action research is embraced to collect and archive tangible materials. The materials which include mbira dzaVadzimu, traditional drums, and hand shakers, traditional objects, still photographs, videos and transcribed mbira songs are preserved in an archive at Midlands State University. The study employs yet another type of archiving system in which intangible heritage of the cultural legacy of mbira dzaVadzimu, which include mbira pieces, skills of playing and making the instrument and indigenous knowledge about mbira dzaVadzimu are preserved in living people through mbira performances in matandaro ceremonies and workshops conducted during mbira conferences, symposium and formal teaching of mbira to students in schools as a way of transmitting the legacy to the young. The study recommends that government and non-governmental organizations should assist in funding the preservation of the cultural legacy of mbira dzaVadzimu. Annual mbira conferences, symposia and workshops should be organized to create an opportunity for the young to interact with culture bearers and scholars. Institutionalization of material culture through archiving should involve the owners of the materials by constantly allowing them to visit the archive and to explain the use of the materials to people who visit the archive.